CHANGES IN THE LUMBAR VERTEBRAL SEGMENT RELATED TO THE CAGE POSITION IN TLIF TECHNIQUE - MATOS, THIAGO DANTAS (Acta Ortop Bras, 2020)
OBJECTIVE: To evaluate the morphological changes on the intervertebral foramen and segmental lordosis related to the transforaminal lumbar interbody fusion (TLIF) positioning. METHODS: PEEK cages were placed in the disc space (L1-S1) of a polyurethane anatomical model. Cages of different heights (8 mm, 10 mm, 12 mm and 14 mm) were positioned in the posterior, medial or anterior part of the vertebral body surface, and the intervertebral foramen and segmental lordosis heights were measured after their insertion. RESULTS: The vertebral foramen height decreased in all positions and heights of the cages in relation to the control. The cage posterior positioning induced a smaller reduction in the vertebral foramen height. Vertebral lordosis tended to increase in relation to the control, and the greatest increase occurred with the cage posterior positioning. CONCLUSION: Cage positioning induces changes in the intervertebral foramen height and in the vertebral segment lordosis. Cage posterior positioning induces a smaller reduction of the intervertebral foramen height and increases the vertebral segment lordosis. Level of evidence III, Therapeutic study.